Diagnostic performance of abdominal CT for diagnosis of pelvic fractures: comparison with pelvic CT. (October 2016) - Yun, Seong Jong; Jin, Wook; Yoon, So Hee; Chun, Young Soo; Cha, Jang Gyu; Koo, Hye-Soo; Park, So Young; Park, Ji Seon; Ryu, Kyung Nam; Lee, Sun Hwa; Shin, Jong Soo
Background: In the emergency department, patients with abdominopelvic trauma inadvertently undergo both abdominal computed tomography (CT) (for intra-abdominal and intra-pelvic organs) and pelvic CT (CT with multiplanar reformation in three orthogonal planes of the bony pelvis). However, the systemic use of CT is concerning given the cumulative radiation dose. Purpose: To evaluate the diagnostic value of abdominal CT in comparison to pelvic CT in patients with suspected pelvic fractures. Material and Methods: Seventy-two patients who underwent abdominal CT and pelvic CT within a 2-week period to evaluate pelvic fractures were included. Two reviewers retrospectively analyzed eight anatomical regions of the pelvic bones on both abdominal CT and pelvic CT over a 1-week interval. The interpretation of pelvic CT scans by two senior musculoskeletal radiologists was considered as the reference standard. Diagnostic performance and inter-observer agreement of both CT scans were evaluated. Results: For reviewers 1 and 2, abdominal CT showed high accuracy (98% and 98%, respectively) as did pelvic CT. For both abdominal CT and pelvic CT, fracture detection in all anatomical regions of the pelvic bones was not significantly different for the two reviewers ( P  ≥ 0.25). Inter-observer agreement for all anatomical regions of the pelvic bones was excellent or good (k = 0.785–1.0). Conclusion: Not only pelvic CT but also abdominal CT is acceptable for detection of pelvic fractures, in spite of its thicker sections and different reconstruction algorithm. Therefore, if abdominal CT has already been performed, additional pelvic CT might no longer be necessary in order to exclude a pelvic fracture.